Verifying the farm size – environment interaction - Fürjész, István (Acta Agraria Debreceniensis, 2006)
With this study, based on experience gained in the United States of America, the author intends to draw attention to the fact that farm size related questions in Hungary, which form an integrant part of farm policies all around the world, cannot and should not be discussed without taking environmental relations into account. In the United States, where the excessive use of agrochemicals poses a great threat to the environment, many researchers claim that the conventional large farm model is now getting outdated. These experts question the social and economic benefits of a large farm oriented farm structure and try to convince researchers arriving from Middle- and Eastern-European countries to reform their thought on optimum farm structure. In their opinion, it is essential to let countries in the region understand that they are not required to follow the US course of large farms, which many experts in the States also would prefer to leave. From the facts presented in this study, it can be concluded that large farms by nature can protect the environment less efficiently than small farms. It is also pointed out that the excessive use of fertilizers, which is a trait often attributed to large farms by researchers throughout the world, do not yet apply to large farms in Hungary. As regards the use of pesticides in Hungary, the unfavorable tendency portrayed in foreign literature is identified in this analysis, according to which the larger the farm involved in field cropping the larger per hectare doses they use to protect their crops.